2022
DOI: 10.1139/cjas-2021-0080
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary organic acids supplementation on growth performance, nutrient digestibility, and gut morphology in weaned pigs

Abstract: This study was conducted to investigate the effects of dietary supplementation with different organic acid (<b>OA</b>) mixtures on growth performance, nutrient digestibility, and gut morphology in weaned pigs. A total of 56 weaned pigs (7.93 ± 1.04 kg body weight) were assigned to four dietary treatments with seven replicates per treatment for a 35-d study conducted over two phases; phase 1 (d 1 to 14) and phase 2 (d 14 to 35). Diets consisted of 1) a corn-soybean meal-basal diet without any additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Organic acids have gained attention in the last few years due to their antimicrobial effects on gut microbiota and improvements in the general performance of pigs [25,38,39]. Several studies summarized by Luise et al [17] suggested that incorporating formic acid as a feed supplement might improve the general performance of nursery pigs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic acids have gained attention in the last few years due to their antimicrobial effects on gut microbiota and improvements in the general performance of pigs [25,38,39]. Several studies summarized by Luise et al [17] suggested that incorporating formic acid as a feed supplement might improve the general performance of nursery pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Formic acid has especially been demonstrated to enhance gastric activity [24], gut health [25], immune status [26], and modulate the microbiota [26], leading to improvement of growth performance in nursery pigs. However, formic acid is corrosive [27,28], thus affecting equipment life, creating handling difficulties, and also causing general irritation to workers [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Blends of medium-chain fatty acids and short-chain organic acids can be utilized by enterocytes as energy sources and attenuate the negative effect of weaning on villus length and crypt depth in pigs [ 34 ]. In weaner pigs, benzoic acid showed an increase in the villus height to crypt depth ratio [ 63 ]. However, in a study by Kong et al [ 64 ], butyric acid did not affect the histology of grower-finishing pigs; only their mucosal depth was larger, and this can be attributed to better gut integrity in older animals.…”
Section: Effect Of Organic Acids and Essential Oils On Pig Performancementioning
confidence: 99%